Reduce the probability of blocking for handoff and calls in cellular systems based on fixed and dynamic channel assignment - Shahir Fleyeh Nawaf; Mohammad Omar Salih; Mohammed Hassan Dervish (Universitas Ahmad Dahlan, 2020)
In cellular systems the high probability of blocking represents a big problem for users, The proposed solution by reducing the blocking probability and investigation cellular systems by method channels assignment. The aim from apaper is studying the effect the channel assignment on the value of blocking probability. The results showed that the fixe channeld assignment gives a large probability of blocking for high loads, While (FCA) reduce probability of blocking for handoff and calls according to cluster size. The cellular system representation in the case of (DCA), in (3-cell reuse) and (7-cell reuse), the results showed the first best way to reduce blocking probability and lead to reduce to approximately zero when loads that are less than 200%. Increasing the cluster size causes to reduce blocking probability. the results showed that the probability blocking for handoff less than from probability of blocking for new calls.